Monoaxial Pedicle Screws Are Superior to Polyaxial Pedicle Screws and the Two Pin External Fixator for Subcutaneous Anterior Pelvic Fixation in a Biomechanical Analysis - Rahul Vaidya; Ndidi Onwudiwe; Matthew Roth; Anil Sethi (Advances in Orthopedics)
Purpose. Comparison of monoaxial and polyaxial screws with the use of subcutaneous anterior pelvic fixation. Methods. Four different groups each having 5 constructs were tested in distraction within the elastic range. Once that was completed, 3 components were tested in torsion within the elastic range, 2 to torsional failure and 3 in distraction until failure. Results. The pedicle screw systems showed higher stiffness (4.008 ± 0.113 Nmm monoaxial, 3.638 ± 0.108 Nmm Click-x; 3.634 ± 0.147 Nmm Pangea) than the exfix system (2.882 ± 0.054 Nmm) in distraction. In failure testing, monoaxial pedicle screw system was stronger (360 N) than exfixes (160 N) and polyaxial devices which failed if distracted greater than 4 cm (157 N Click-x or 138 N Pangea). The exfix had higher peak torque and torsional stiffness than all pedicle systems. In torsion, the yield strengths were the same for all constructs. Conclusion. The infix device constructed with polyaxial or monoaxial pedicle screws is stiffer than the 2 pin external fixator in distraction testing. In extreme cases, the use of reinforcement or monoaxial systems which do not fail even at 360 N is a better option. In torsional testing, the 2 pin external fixator is stiffer than the pedicle screw systems.